2019
DOI: 10.1097/md.0000000000014618
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics of renal solitary fibrous tumor

Abstract: To analyze the clinical characteristics, treatment modalities and outcomes of adult renal solitary fibrous tumors (SFT) treated at a single institution. Demographic, diagnostic, surgical, and pathological findings of patients who had undergone radical nephrectomy (RN) due to renal SFT were collected from the database of a single institution and were retrospectively reviewed. Ten patients (6 men and 4 women) were diagnosed with renal SFT in our institution between January 1, 2000 and December 31, 2016. The mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(18 citation statements)
references
References 24 publications
(30 reference statements)
0
18
0
Order By: Relevance
“…The NAB2–STAT6 fusion is the molecular hallmark (Fig. d) of SFTs . Although Barthelmess et al detected a significant association between the NAB2ex6‐ STAT6ex16/17 variant and malignancy in SFTs, other authors have reported that no fusion variants are associated with malignancy …”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…The NAB2–STAT6 fusion is the molecular hallmark (Fig. d) of SFTs . Although Barthelmess et al detected a significant association between the NAB2ex6‐ STAT6ex16/17 variant and malignancy in SFTs, other authors have reported that no fusion variants are associated with malignancy …”
Section: Introductionmentioning
confidence: 97%
“…Many of the histological variants reveal a focal patternless architecture, and variably fibro‐collagenous stroma . NAB2‐STAT6 was discovered as a novel fusion gene of SFTs, and STAT6 immunoexpression has been established as a surrogate marker of the NAB2‐STAT6 gene fusion, expression of this protein representing a very sensitive and specific diagnostic tool …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations